The novel allele, HLA‐DQB1*02:27, identified in a German cord blood donor and his mother. Issue 6 (22nd October 2013) - Strobel, J.; Ringwald, J.; Hauck, B.; Eckstein, R.; Zingsem, J.
<x xml:space="preserve">Abstract</x> The novel allele HLA‐DQB1*02:27 identified in two related individuals of Caucasian origin is described.